Synthesis and Catalytic Performances of a Novel Zn-MOF Catalyst Bearing Nickel Chelating Diimine Carboxylate Ligands for Ethylene Oligomerization - Suyan Liu (Journal of Spectroscopy, 2015)
A novel Zn-MOF[Zn3(OH)2L2] was synthesized from dicarboxylate ligands with diimine groups (1,4-bis(4-CO2HC6H4)-2,3-dimethyl-1,4-diazabutadiene). The physicochemical properties of the material were characterized by a series of technologies including XRD, SEM, and ICP. In order to adapt to the ethylene oligomerization process, a catalyst [Zn3OH2L1Ni2] (denoted as Cat.A) possessing active Ni2+ centers was prepared by a postsynthetic treatment method using dichloride nickel as a nickel source in this work. For comparison, α-diimine ligands with/without dicarboxylic acid groups reacted with dichloride nickel to obtain homogenous Cat.B and Cat.C, respectively. The effects of reaction parameters, including n(Al)/n(Ni), temperature, and pressure on the oligomerization activities and oligomers distribution were investigated. The results demonstrated that all of catalysts used with diethylaluminum chloride were active for the ethylene oligomerization. Among them, Cat.A and Cat.B showed higher catalytic activities and higher selectivities to low-carbon α-olefins at atmospheric pressure. The Cat.A exhibited the optimal catalytic activity [6.7 × 105 g/(mol·Ni·h·atm)] for C4 (91.8%) under the conditions of Al/Ni = 1500, P = 1.0 atm, T = 20°C. In addition, Cat.A and Cat.B presented large amount of ethylene polymer, while Cat.C had a higher catalytic activity of ethylene oligomerization at high pressure.